PERANCANGAN SISTEM INFORMASI PENDAFTARAN AGEN DAN ORDER PRODUK PT MACAKAL PANGAN SEJAHTERA CIAMIS DENGAN METODE PROTOTYPE - Deddy Supriadi; Iqbal Dzulfiqar Iskandar; Erwin Triyana (Jurnal Informatika Teknologi dan Sains (Jinteks), 2023)
The rapid advancement of information technology is currently encouraging companies to always adapt to technological developments. In this regard, the company PT. Macakal Pangan Sejahtera management of business processes is still done manually. The purpose of this research is to design a website-based information system that can make it easier for users to register to become agents, tidy up agent data that has been registered and make product order transactions by agents to be more organized and can make order reports easily and efficiently. The method applied using the prototype method. The research results have proposed the design of an agent registration information system and product orders at PT. Macakal Pangan Sejahtera as a solution to problem solving. As an evaluation, interface testing is carried out on the admin page, registration and agent pages. test results have a success value of 100%. The research results concluded that by proposing a website-based agent registration and product order information system design, companies can develop business processes more quickly and efficiently.